Use of romiplostim in patients with chronic idiopathic thrombocytopenic purpura during perioperative period. Issue 7 (July 2015) - Ramakrishna, R.; Rehman, A.; Ramakrishna, S.; Alexander, W.; Yeo, W. W.
Abstract Introduction In patients with chronic idiopathic thrombocytopenic purpura (cITP), the platelet count tends to be quite variable and, in the majority of cases, specific therapy is not warranted on a regular basis. However, patients with low platelet count (<30 nL) or with bleeding complications would require therapy, such as prednisolone, intravenous immunoglobulin infusions, splenectomy and/or immunosuppression. Romiplostim, a thrombopoietin agonist, has also proven to be useful in improving platelet counts. cITP can be associated with bleeding complications perioperatively. As such, a higher platelet count is warranted (approximately 80 nL), particularly for invasive surgeries, such as orthopaedic surgery, cardio‐thoracic surgery, head and neck surgery and abdominal surgery, where risk of bleeding is quite high already. Aim The aim of this study is to evaluate the safety and efficacy of short‐term use of romiplostim, perioperatively. Methods Patients with chronic ITP requiring major surgical interventions were enrolled in the study. Patients with malignancies or myelodysplastic syndromes, major bleeding disorders, under 18 years of age or pregnancy were excluded. Conclusion This study has shown that the use of romiplostim is safe and effective in improving platelet counts preoperatively and that this could achieve excellent haemostasis, with no associated bleeding complications or rebound thrombocytopenia. A larger study involving multiple centres is required to verify these findings.